Investigating the Ideology of Indonesian Universities through the Vision and Mission Statements: A Corpus-Assisted Discourse Study - Sindy Alicia Gunawan; Layli Hamida (Masyarakat Linguistik Indonesia, 2023)
Literatures have shown that discursive investigation on universities’ vision and mission statements can reveal the universities’ ideologies as well as the prevailing sociopolitical factors in the country. However, there is no such investigation within Indonesian higher education discourse yet. This study seeks to fill the gap by conducting a corpus-assisted analysis on the vision and mission statements of 100 Indonesian universities. By implementing CADS procedures, this study combines corpus linguistics techniques and ideological discourse analysis approach. The final results reveal the social responsibility of Indonesian universities to support public welfare and the emergence of internationalization movement within the educational system of the country, denoting collectivism and neoliberalism as ‘negotiating’ ideologies within the institutional discourse. It is related to none other than the view that universities are institutional bodies that cannot be stagnant as they must always be progressing towards the current development of society and even the world.